Fertility preservation in Malaysian pediatric cohort: a survey of healthcare providers’ knowledge, practice, attitude, perceptions and barriers - Ali, Anizah; Lee, Yew Kong; Alias, Hamidah; Zainuddin, Ani Amelia (Frontiers in Pediatrics, 2024)
Introduction Impaired future fertility potential secondary to gonadotoxic therapies for childhood cancer is a shattering aftermath faced by childhood cancer survivors. Fertility preservation (FP) has emerged as a key to mitigate this unwelcomed sequelae. FP services catering to the needs of children and adolescents (C&A) population in developing countries are limited. Malaysia recently launched its pioneering pediatrics FP services. Aims of study To evaluate healthcare providers’ (HCPs) FP knowledge, practice behaviors, attitudes, perceptions, and barriers towards FP counseling/services (C/S) for the C&A cohort. Methods A questionnaire-based study was conducted utilizing a questionnaire consisting of 51 items which was adapted from G.Quinn et al. The questionnaire was distributed both online and physically amongst HCPs in a tertiary center. Ethical committee approval was granted by the Research Ethical Committee, Universiti Kebangsaan Malaysia. Results A total of 102 HCPs completed the questionnaires. The majority of respondents were Malays (74.5%), females (80.4%), gynecology/pediatrics specialty (76.5%), and had children (88.2%). Nearly 72% of HCPs demonstrated good knowledge of FP. Almost 73% of HCPs consulted reproductive specialists (RES) on potential fertility issues and over 80% of HCPs referred patients who enquired on fertility issues to RES. Only 17% of HCPs practiced FP discussion, 12% reported no available person to discuss FP, and 10% of HCPs were unaware of who to discuss FP with. Patients’ inability to afford FP (30.4%) tops the list of barriers to FP C/S, followed by limited available information on FP for patients (17.6%) and patients too ill to delay treatment (12.7%). Most HCPs (88.2%) demonstrated unfavorable attitudes towards FP C/S. Discussions In general, the majority of our HCP respondents demonstrated good current FP knowledge and practice behaviors. Mitigating several controversial issues in FP would improve HCPs’ attitude towards FP. Main barriers to the uptake of FP C/S for C&A were patient and resource barriers. Addressing these issues by funding aid for FP procedures, increasing FP knowledge dispersion, as well as developing age-appropriate FP-related educational materials would improve FP service provision for C&A in the future. Conclusions In conclusion, successful corrective action combined with strategic planning points to a promising future for Malaysia's FP services provision for C&A.